Detection, virulence genes and antimicrobial resistance of Yersinia enterocolitica in sheep and goat raw milk. (June 2021) - Piras, Francesca; Spanu, Carlo; Sanna, Rita; Siddi, Giuliana; Mocci, Anna Maria; Demontis, Mariella; Meloni, Maria Pina; Spanu, Vincenzo; De Santis, Enrico Pietro Luigi; Scarano, Christian
Abstract: The aim of this study was to evaluate the prevalence of Yersinia enterocolitica in sheep and goat raw milk in Sardinia (Italy). Overall, 738 samples from bulk milk tanks were collected: 507 raw sheep milk samples and 231 raw goat milk samples. Y. enterocolitica was detected from 24/507 (4.8%) raw sheep milk and 24/231 (10.4%) goat milk samples. Prevalence was significantly higher ( P  < 0.01) in goat milk than in sheep milk. Biotyping of Y. enterocolitica isolates identified only biotype 1A. The most common virulence genes were investigated: yst B gene was found in 42/48 (87.5%) and inv in 40/48 (83.3%) strains. All the isolates were susceptible to ciprofloxacin, nalidixic acid, sulphonamide, tetracycline and trimethoprim. Five AMR profiles were identified showing resistance to amoxicillin-clavulanic acid, ticarcillin, cephalexin, cefoxitin and ceftriaxone. Resistance to third generation cephalosporins is of particular concern as they are recommended for therapeutic use in case of human illness.